A taxonomic Revision of the genus Graellsia (Brassicaceae, tribe Thlaspideae) - Esmailbegi, Shokouh; Lysak, Martin A.; Rahiminejad, Mohammad Reza; Mirtadzadini, Mansour; Mummenhoff, Klaus; Al-Shehbaz, Ihsan A. (Phytotaxa, 2017)
Graellsia includes nine species, of which five (three endemic) are native to Iran. The new species G. isfahan is described and illustrated, and its relationship to the Turkish endemic G. davisiana is discussed. The new combination G. longistyla is proposed, and the lectotypes of G. graellsiifolia, G. integrifolia, and G. stylosa are designated.